A cleft lip and palate gene, Irf6, is involved in osteoblast differentiation of craniofacial bone. Issue 3 (7th February 2019) - Thompson, Jake; Mendoza, Fabian; Tan, Ethan; Bertol, Jessica Wildgrube; Gaggar, Arju S; Jun, Goo; Biguetti, Claudia; Fakhouri, Walid D.
Abstract : Background: Interferon regulatory factor 6 ( IRF6 ) plays a critical role in embryonic tissue development, including differentiation of epithelial cells. Besides orofacial clefting due to haploinsufficiency of IRF6, recent human genetic studies indicated that mutations in IRF6 are linked to small mandible and digit abnormalities. The function of IRF6 has been well studied in oral epithelium; however, its role in craniofacial skeletal formation remains unknown. In this study, we investigated the role of Irf6 in craniofacial bone development using comparative analyses between wild‐type (WT) and Irf6 ‐null littermate mice. Results: Immunostaining revealed the expression of IRF6 in hypertrophic chondrocytes, osteocytes, and bone matrix of craniofacial tissues. Histological analysis of Irf6 ‐null mice showed a remarkable reduction in the number of lacunae, embedded osteocytes in matrices, and a reduction in mineralization during bone formation. These abnormalities may explain the decreased craniofacial bone density detected by micro‐CT, loss of incisors, and mandibular bone abnormality of Irf6 ‐null mice. To validate the autonomous role of IRF6 in bone, extracted primary osteoblasts from calvarial bone of WT and Irf6 ‐null pups showed no effect on osteoblastic viability and proliferation. However, a reduction in mineralization was detected in Irf6 ‐null cells. Conclusions: Altogether, these findings suggest an autonomous role of Irf6 in regulating bone differentiation and mineralization. Developmental Dynamics 248:221‐232, 2019. © 2019 Wiley Periodicals, Inc. Key Findings: Irf6 is expressed in osteocytes and hypertrophic chondrocytes of craniofacial tissues. Loss of Irf6 leads to a reduction in the number embedded osteocytes and TRAP+ osteoclasts in bone matrices. Irf6‐null mice exhibit delay and reduction in bone mineralization, loss of incisors and mandibular hypoplasia.